Role of Women in Purchasing FMCG Products in Rural Markets (Global Journal of Management and Business Research, 2021)
The aim of this research study is to identify which role women plays in purchasing FMCG products in rural markets in India. Rural markets in India is growing rapidly and provides chance for the markets to grow in rural markets. Markets are aware about the characteristics of rural markets and they are not leaving any stone to leverage the profit from rural markets. There are lot of changes happening in rural markets because of rural development, increased literacy level and rising in income levels etc. The consumers from rural markets are looking for value for money and they are making choices for FMCG purchase accordingly.
Keywords: rural markets; FMCG products; rural women; purchase decision